PENGARUH ADSORPSI BESI (Fe) TERHADAP MORFOLOGI ADSORBEN - Mycelia Paradise; Yudha Agung Pratama; Faisol Mukarom; Triyono (Institut Teknologi Nasional Yogyakarta, 2024)
This research aims to analyze the effect of the adsorption process on the morphology of adsorbents consisting of a mixture of claystone, zeolite, and activated coconut shell charcoal in adsorbing Fe ions from acid mine drainage. The adsorption process was carried out in a batch system using a hotplate stirrer on a laboratory scale. The experimental method was applied to evaluate the characterization of the adsorbent surface morphology before and after the adsorption process using a Scanning Electron Microscope (SEM). The research results showed significant changes in the adsorbent surface morphology after the adsorption process, indicated by differences in the structure and topography of the adsorbent.